APPLICATION OF THE PROPORTIONALITY PRINCIPLE IN COMMERCIAL CONTRACTS TO ENSURE JUSTICE FOR THE PARTIES - Niru Anita Sinaga (Faculty of Law, Universitas Pekalongan, 2023)
Contracts play a very significant function in business. It is envisaged that applying the proportionality principle will aid in the realization of the contract's objectives and functions. The principle of proportionality governs the exchange of rights and obligations between parties in accordance with their proportions or parts, and it applies throughout the contract process, including the pre-contractual stage, contract formulation, and contract execution. Commercial contracts emphasize characteristics of partnership and business continuity, with the parties exchanging their rights and obligations in a fair and reasonable manner. To build a fair and mutually advantageous contractual partnership, ensure that the parties' interests (rights and obligations) are exchanged in balance. The notion of proportionality is vital not only for creating contracts that are just and mutually advantageous (substantial justice), but also for emphasizing fairness (fairness in procedures). The integration of contract law concepts is an analytical technique for dissecting the presence of contracts formed by the parties in order to manage the parties' various interests in a proportional manner